2021
DOI: 10.3991/ijet.v16i24.24121
|View full text |Cite
|
Sign up to set email alerts
|

A Scenario of the Formative E-assessment Based on the ARCS Model: What Is the Impact on Student Motivation in Educational Context?

Abstract: The purpose of this research is to measure the motivation of nursing students, option: multi-skilled nurse (n=58), following their participation in an e-learning activity in the form of formative quizzes. The pedagogical scenario was based on Keller's ARCS motivation model. Data were collected through the IMMS questionnaire adopted from the ARCS model. The results show that the students were motivated by the e-learning activity (mean score = 4.22±, 51091), and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The first step in NLQAS architecture is to understand the student's question asked by the user rather than being given the chance to enter the system to find the answer. It can be done using cosine similarity techniques, such as the similarity between two documents [27]. The three most relevant documents using cosine similarity were obtained based on the evaluation value.…”
Section: Methodsmentioning
confidence: 99%
“…The first step in NLQAS architecture is to understand the student's question asked by the user rather than being given the chance to enter the system to find the answer. It can be done using cosine similarity techniques, such as the similarity between two documents [27]. The three most relevant documents using cosine similarity were obtained based on the evaluation value.…”
Section: Methodsmentioning
confidence: 99%
“…In this phase, the goal is to develop educational content that matches the specific learning needs of the students. According to a study carried out by Lajane et al (2021) that assessed the motivation of nursing students in utilizing e-assessment, it was found that students perceived online quizzes as highly relevant. The relevance factor received a score of 3.93, with the lowest score being 3.8 and the highest score being 4.27.…”
Section: Relevant Factor and Effectiveness Of Online Learningmentioning
confidence: 99%
“…Confronted with a heterogeneous students population with an eager desire to learn and meet important challenges in their academic careers, and also with the increased demand for training that perfectly responds to societal changes [13], [14], teachers are supposed to innovate in pedagogy and thus, adopt constructivist and socio-constructivist pedagogical approaches, such as the Flipped Classroom (FC) [14], [15]. However, one of the necessary conditions for the successful implementation of a pedagogical innovation is precisely the motivation and engagement of the students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To this end, several pedagogues in educational sciences have attempted, through their theories, to define the concept of motivation and consequently to identify its indicators and determinants, to develop valid scales that facilitate the identification of the motivational profile with the perspective of readjusting and improving the quality of teaching and learning [15].…”
Section: Literature Reviewmentioning
confidence: 99%